The Philosophy of Multicultural Science as a Foundation for Strengthening Counselor Competence: A Literature Review in the Context of Guidance and Counseling - Rahmadanti, Ananda Dwi; Prasetya, Akhmad Fajar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Indonesia’s multicultural context poses complex challenges for guidance and counseling practices, requiring counselors to possess not only technical skills but also strong multicultural competence grounded in philosophical awareness. However, the philosophical foundations of multicultural counselor competence remain underexamined in Indonesian literature. This study aims to analyze multicultural counselor competence through the perspective of multicultural philosophy of science, focusing on ontological, epistemological, and axiological dimensions. Using a systematic-narrative literature review, this study analyzed peer-reviewed national and international publications from 2015–2025 related to multicultural counseling, counselor competence, and philosophical perspectives. Qualitative content analysis was employed to identify key conceptual themes. The findings indicate that multicultural counselor competence encompasses cultural self-awareness, cultural knowledge, adaptive counseling skills, and a commitment to social justice. These elements are philosophically rounded in the recognition of human diversity, culturally constructed knowledge, and ethical responsibility. This study highlights the need to integrate philosophical foundations into counselor competence development and contributes a synthesized conceptual framework to support more reflective and context-sensitive counselor education in multicultural settings.